PENGARUH POLARITAS MEDAN LISTRIK EKSTERNAL DAN SUDUT POLARISASI LASER DIODA UNTUK PENGAMATAN EFEK KERR - Wibowo, Hari; Sugiyanto, Eko; Firdausi, K. Sofjan; Marhaendrajaya, Indras (BERKALA FISIKA, 2006)
An identification of non linear optics of some material has been carried out. The samples used here are mineral water, salt solution, and sugar solution for various concentrations. A static applied external field E is adjusted to left and right direction. And also, the direction of electric field of laser is varied against E. The magnitude of E used in the experiment is produced by a DC high voltage (0-10 kV) applied on two identical parallel plates. A source of light to the samples is a diode laser of 645 nm and 5 mW. The change of polarization angle of laser b after through the samples is the optical property to be identified. Both of mineral water and salt solution, the effect of polarity of E shows identical results of b vs. E. In case of sugar solution, we obtain a positive gradient for right polarity and negative gradient for left polarity of E. Key words: non linear optics, polarization, polarization angle, Kerr Effect